Islamic ethics and liberal democracy: a critical analysis of Mustafa Akyol’s perspectives - Mohamed Zacky, Mohamed Fouz; Ilyas, Inaz (IIUM Press, 2024)
The Arab Spring and its aftermath sparked a renewed interest among scholars and thinkers in exploring the potential compatibility between Islam and liberal democracy. This led to a series of debates both supporting and critiquing this idea. This study focuses on the ideas of Mustafa Akyol, a prominent scholar who actively engaged in the ongoing debate on reforming Islamic political thought over the past decade. By closely examining his primary work, Reopening Muslim Minds, this paper argues that Akyol not only presents a clear intellectual framework for demonstrating the convergence of Islam and liberal democracy but also explores how Islam can contribute to shaping modern multicultural societies. However, this study also suggests that Akyol's failure to critically examine modernity and liberalism as philosophical project to the same extent as he did with Islamic intellectual tradition resulted in a lack of genuine dialogue between Islam and liberal democracy in his work. Additionally, the paper argues that Akyol's analysis of Islamic intellectual tradition is somewhat flawed, particularly in his binary take onclassical Islamic theological and philosophical movements.